2014
DOI: 10.1074/jbc.m114.583450
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Stimulates Duox1 Activity through GPRC6A in Skin Keratinocytes

Abstract: Background:The molecular mechanisms underlying the non-genomic activities of testosterone in keratinocytes are unknown. Results: Testosterone stimulates Duox1 activity through GPRC6A leading to cell death in skin keratinocyte. Conclusion: These results support an understanding of the molecular mechanism of testosterone-dependent apoptosis through Duox1-induced H 2 O 2 generation. Significance: These results provide a novel signaling cascade of testosterone-mediated redox regulation in keratinocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…) and ‐independent (Ko et al . ) mechanisms. This includes NADPH‐oxidase‐dependent ROS generation in ECs (Costa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and ‐independent (Ko et al . ) mechanisms. This includes NADPH‐oxidase‐dependent ROS generation in ECs (Costa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The simplest explanation of a possible AR-mediated NO suppressive effect is DHT induction of reactive oxygen species (ROS). Testosterone has been shown to induce ROS formation by both AR-dependent (Montezano et al 2015) and -independent (Ko et al 2014) mechanisms. This includes NADPH-oxidase-dependent ROS generation in ECs (Costa et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For measurement of intracellular ROS or H 2 O 2 , cells were incubated in the dark for 30 min with 5 mM 5,6-chloromethyl-2′,7′-dichlorodihydrofluorescein diacetate (Molecular Probes) or 5 mM Peroxy Orange-1 (PO-1) (Tocris Bioscience) for 15 min in phenol red-free medium, respectively [29,30]. For analysis of cell death, cells were labeled with fluorescein isothiocyanate (FITC)-Annexin V plus propidium iodide (PI) in annexin binding buffer at 25°C for 15 min, according to the manufacturer's instructions (FITC Annexin V apoptosis detection kit; BD Biosciences).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…As suggested by Barton et al (11), the orphan G protein-coupled receptor GPRC6A, which has been shown to mediate nongenomic responses to testosterone, might be a possible candidate to mediate the rapid, AR-independent effects of testosterone on ROS generation in VSMC (11). In addition, testosterone induces Duox1 activation through GPRC6A in keratinocytes that leads to H 2 O 2 generation (104).…”
Section: Other Mechanisms: Testosterone and Ros Generation/oxidative mentioning
confidence: 96%